Switzerland : 2010 Article IV Consultation; Staff Report; Public Information Notice on the Executive Board Discussion; Statement by the Executive Director for Switzerland, and Informational Annex. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
Switzerland was hard hit by the global crisis; however, the 1.5 percent contraction in 2009 compares favorably with most industrial countries. This 2010 Article IV Consultation highlights that after a year-long decline in real GDP, the economy exited the recession in mid-2009. In response to the crisis, the authorities took a series of actions in a broad range of policy areas. Financial sector measures also helped to stabilize financial markets and reduce systemic risk. The authorities are now contemplating how to exit from the current accommodative stance.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet